Pelatihan Pembuatan Media Pembelajaran Interaktif dengan Ispring Presenter Bagi Guru SDN Sidorejo I dan SDN Kebonsari III Kecamatan Tuban Kabupaten Tuban - Wiratsiwi, Wendri; Sari, Mega Puspita (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Researchers chose these two elementary schools as partners because they found similar problems between one primary school and another primary school. The problems found were the ability of teachers at SDN Sidorejo I and SDN Kebonsari III in the knowledge of technology-based learning media is still low and the utilization of technology facilities for teachers at SDN Sidorejo I and SDN Kebonsari III to support the content of teaching materials to improve the quality of teaching and learning process is still low low. The method of implementing this training was carried out with several steps of activities, namely (1) The initial activity began with the introduction of the Ispring Presenter learning media and demonstrations. The next activity was to provide mentoring twice. Assistance is carried out with guidance and practice methods; (2) The next activity is each teacher presenting how to operate various forms of interactive and innovative questions that have been made according to the subjects being taught. The existence of this training can improve the ability of teachers in mastering material about Ispring Presenter and its use which shows an average value of 93.85 for SDN Sidorejo I and by 90.90 in SDN Kebonsari III. The teacher's response to the training in making instructional media using Ispring Presenter from four indicators shows a positive response.